Simulation and Modeling with Designing for the Proportional, Integral and Derivative Control of Industrial Robotic Arm by Using MATLAB/Simulink - Shneen, Salam Waley; Juhi, Hasan H.; Najim, Hiba Ali (International Journal of Robotics and Control Systems, 2024)
This study aims to develop a control system for a robot arm, designed to perform precise movements along a predefined path, suitable for various industrial applications. The robot arm's movements are driven by three electric motors, each responsible for controlling a joint, enabling the arm to follow the required path accurately. To manage the complexity of multiple motors and dynamic movement requirements, an automated control system has been developed, tailored to meet the specific demands of the proposed task. A highly efficient, reliable, and safe control system design is being developed and simulated to evaluate its effectiveness in executing the required path. A simulation model is being constructed to assess the system's ability to follow the prescribed path, its responsiveness to disturbances and transient conditions, and the overall accuracy of the arm's movements. Simulation results will be analyzed to determine the system's performance across various scenarios, evaluating its adaptability to the work environment and its ability to achieve tasks with high accuracy, thereby enhancing system effectiveness.